Endometriosis Is Associated with Functional Polymorphism in the Promoter of Heme Oxygenase 1 (HMOX1) Gene - Milewski, Łukasz (Cells, 2021)
Endometriosis is a common gynecological disorder characterized by the ectopic growth of endometrial-like tissue outside the uterine cavity. Etiopathogenesis of endometriosis is poorly understood; it is plausible, however, that the disease may be associated with oxidative stress related to local heme and iron metabolism. Therefore, the aim of the study was to reveal a possible association of endometriosis with a stress-inducible heme oxygenase 1 (HMOX1). For this purpose, 228 patients with clinically confirmed endometriosis and 415 control parous women from general Polish population were examined for functional –413A>T (rs2071746) single-nucleotide polymorphism (SNP) and (GT)(n) dinucleotide repeat length polymorphism in the promoter of HMOX1 gene. In addition, –413A>T SNP was assessed by the specific TaqMan(®) SNP Genotyping Assay, and (GT)(n) polymorphism was determined by PCR product size analysis. We found that endometriosis is associated with an increased frequency of −413A(GT)(31,32) haplotype (OR (95%CI) = 1.27 (1.01–1.60), p = 0.0381) and −413A(GT)(31,32) homozygous genotype [OR (95%CI) = 1.51 (1.06–2.17), p = 0.0238]. These data suggest that endometriosis is associated with functional polymorphism of HMOX1 gene, and this gene may play a part in the pathogenesis of this disorder.